2010
DOI: 10.1152/jn.01090.2009
|View full text |Cite
|
Sign up to set email alerts
|

Population Response Profiles in Early Visual Cortex Are Biased in Favor of More Valuable Stimuli

Abstract: Serences JT, Saproo S. Population response profiles in early visual cortex are biased in favor of more valuable stimuli. J Neurophysiol 104: 76 -87, 2010. First published April 21, 2010 doi:10.1152/jn.01090.2009. Voluntary and stimulus-driven shifts of attention can modulate the representation of behaviorally relevant stimuli in early areas of visual cortex. In turn, attended items are processed faster and more accurately, facilitating the selection of appropriate behavioral responses. Information processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
75
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 103 publications
(108 reference statements)
18
75
1
Order By: Relevance
“…We always placed the neurons' RFs on the curve but not on the circle itself, and the increased neuronal activity must therefore have spread from the circle onto the curve, suggesting that reward information influences neuronal activity in an object-based manner. Effects of reward value have been reported previously for rat area V1 (27) and also in human visual cortex with fMRI (28,39,40). The findings of this study are compatible with these previous results, but they also go beyond by showing that reward effects in V1 are mostly driven by relative value, which is a quantity that is useful for the guidance of choice behavior.…”
Section: Discussionsupporting
confidence: 92%
“…We always placed the neurons' RFs on the curve but not on the circle itself, and the increased neuronal activity must therefore have spread from the circle onto the curve, suggesting that reward information influences neuronal activity in an object-based manner. Effects of reward value have been reported previously for rat area V1 (27) and also in human visual cortex with fMRI (28,39,40). The findings of this study are compatible with these previous results, but they also go beyond by showing that reward effects in V1 are mostly driven by relative value, which is a quantity that is useful for the guidance of choice behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have demonstrated that sensory processing in the cortex can be potentiated when associated with reward (e.g. Mogami and Tanaka, 2006;Hui et al, 2009;Franko et al, 2010;Hickey et al, 2010;Serences and Saproo, 2010;Weil et al, 2010). Our finding that the cortex can transmit information to DA neurons via the SC thus provides a mechanism by which short-latency sensory signals relayed to DA neurons can reflect stimulus value.…”
Section: Functional Implicationssupporting
confidence: 52%
“…Although rarely emphasized, visual cortex activation is consistently apparent in studies using visual cues to probe craving (11,12), and visual cortex response to high-calorie foods has been shown to be modulated by positive affect (13). Given top-down influences over visual processing (14) and evidence that higher-value targets recruit greater visual activation (15), it is also reasonable to hypothesize that altered valuation mediates the robust effect that food cues had on activity within the visual cortex. Thus, greater food-cue reactivity in the visual cortex after fructose than glucose may indicate a greater incentive value of food cues.…”
Section: Discussionmentioning
confidence: 99%